Determination of the concentration of natural and artificial radionuclides in the soil of the Campus of the Federal University of Sergipe - Cardoso, Leandro Xavier; Souza, Susana Oliveira; Ferreira, Fernanda C L; Ferreira, Orlando Christino; Barboza, Elenilson (Scientia Plena, 2011)
Natural radionuclides are not only found scattered in the earth's crust but in all environments on the planet: soil, water and atmosphere, and leading from the natural radioactive series of 238U and 232Th, and the 40K. However, the artificial radionuclides in the vast majority produced since the 40’s and released into the environment by nuclear tests, were spread throughout the globe by the process known as "fallout." In view of the lack of geochemical data in the state of Sergipe, this work was done in order to analyze the activity of radionuclides in the soil of the Federal University of Sergipe, located at the city of São Cristovão. The collection of samples was performed at five points on the campus of the university, which were sent to the Eletronuclear's Environmental Monitoring Laboratory, located in Paraty - RJ, and analyzed by gamma spectrometry, thereby obtaining the radioactive elements present in samples. Keywords: artificial radionuclides, 238U, concentration.